2020
DOI: 10.3390/su12156060
|View full text |Cite
|
Sign up to set email alerts
|

How Attractive for Walking Are the Main Streets of a Shrinking City?

Abstract: This research assesses the way main streets are perceived and used by pedestrians in an industrial, Central-European city—Ostrava in Czechia. The city has recently experienced shrinkage and changing patterns of socio-economic exchange, reason why this research is timely and needed in view of city center regeneration. Four main streets have been purposefully selected for this study. The research methods include questionnaires with street users (n = 297), direct observations of human activities and pedestrian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Only joint planning and implementation efforts may result in well-structured interventions, which deal both with the site infrastructure (i.e., related to transportation) and with the transformation of the area into a truly multi-use type of district (Bach-Głowińska et al, 2020). This should also result in developing pedestrian-oriented structures, well served by the pub-lic transit (Istrate et al, 2020;Viderman & Knierbein, 2020). Developed according to the principles of placemaking and public space design, these can serve as the new type of urban center of metropolitan importance (Carmona, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Only joint planning and implementation efforts may result in well-structured interventions, which deal both with the site infrastructure (i.e., related to transportation) and with the transformation of the area into a truly multi-use type of district (Bach-Głowińska et al, 2020). This should also result in developing pedestrian-oriented structures, well served by the pub-lic transit (Istrate et al, 2020;Viderman & Knierbein, 2020). Developed according to the principles of placemaking and public space design, these can serve as the new type of urban center of metropolitan importance (Carmona, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…When studies on the threshold space are examined, it is observed that several common techniques are utilized, the most prevalent of which are the observation method (Danilina & Privezentseva, 2020;Akartuna, 2017;Şevik, 2018) and the processing of observation data on maps (Eltan et al, 2015;Akartuna, 2017;Şevik, 2018). The method of processing user observation data on the map is called the "behavior mapping technique" (Eltan et al, 2016;Akartuna, 2017;Sevik, 2018;Barker, 1968;Ittelson, Rivlin, & Prohansky ,1970;Goličnik Marušić, 2010;Guinther et al, 2014;Al-Maimani et al, 2014;Mandel, 2016;Karadeniz et al, 2018;Ozbil et al, 2018;Gharib, 2019;Onojeghuo et al, 2019;Istrate et al, 2020;Wang & Wu, 2020;Cosco et al, 2010;McQuilkin, 2016;Van der Spek et al, 2009;Valkenet et al, 2022;Milke et al, 2009;Cox et al, 2018;Arsan & Kepez, 2017;Liao et al 2022). Behavior mapping technique was first developed at the end of the 1960s, by environmental and behavioral researchers such as Barker (1968) and Ittelson, Rivlin, & Prohansky (1970).…”
Section: On-site Observation and Behavior Mapping Techniquementioning
confidence: 99%
“…This all makes high streets a "particularly wicked problem" [6] (p. 18), as responsibility for high streets has been "disastrously fragmented"-with different stakeholders and agencies tending to their own narrow viewpoints and with barely anyone taking a holistic approach [6] (p. 18). This, however, makes the high street not only a problem in itself, but also a key part of the solution to broader urban problems-a kind of urban laboratory for walkability, resilience, and sustainability [3,[6][7][8][9][10][11].…”
Section: Introduction: the High Street Sustainability Questionmentioning
confidence: 99%